Kajian Alkitab terhadap Pernikahan Sesama Jenis - Ataupah, Teresia Vinti; Tloim, Aldes Samor; Malaire, Fentri; Obehetan, Yeheskiel (Vieka Wahana Semesta, 2025)
This article aims to examine and formulate a consistent church stance on the issue of same-sex marriage, a topic that has generated significant debate among Christians. Using an in-depth library study, this research analyzes a variety of relevant theological texts and resources, all obtained from reliable library references. We explore the doctrinal foundations, beginning with the Old Testament creation narrative, which fundamentally establishes marriage as a unique bond between a man and a woman. This study also extends to the New Testament, where the writings of the Apostle Paul, particularly Romans 1:26-27 and 1 Corinthians 6, explicitly and consistently condemn homosexual practices. The results of this research clearly demonstrate that the Bible, in both the Old and New Testaments, consistently rejects and does not recognize same-sex marriage as a legitimate relationship. Therefore, the conclusion drawn is that a church faithful to and aligned with the biblical foundation must firmly reject the legalization or celebration of same-sex marriage. This rejection is based on the deep conviction that the church cannot set aside the teachings of Scripture to accommodate contemporary cultural norms but must adhere to God-revealed truth as the foundation of its ethics and doctrine.